Establishment and functions of DNA methylation in the germline - Stewart, Kathleen R; Veselovska, Lenka; Kelsey, Gavin (Epigenomics, 2016)
Epigenetic modifications established during gametogenesis regulate transcription and other nuclear processes in gametes, but also have influences in the zygote, embryo and postnatal life. This is best understood for DNA methylation which, established at discrete regions of the oocyte and sperm genomes, governs genomic imprinting. In this review, we describe how imprinting has informed our understanding of de novo DNA methylation mechanisms, highlight how recent genome-wide profiling studies have provided unprecedented insights into establishment of the sperm and oocyte methylomes and consider the fate and function of gametic methylation and other epigenetic modifications after fertilization.
Keywords: Genomic Imprinting; transgenerational inheritance; metylace DNA; histonový kód; DNA Methylation; DNA methylation; genomový imprinting; zárodečné buňky; Germ Cells; Animals; embryo; lidé; Histone Code; spermatogenesis; oogenesis; Humans; imprinting; zvířata